Sustaining Openness: Research Data, Infrastructure and Institutional Commitment - Both, Joeri (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
This case study outlines how Vrije Universiteit Amsterdam developed integrated RDM services through researcher profiling, cultural-change strategies, community building, and tailored infrastructures. The programme produced sustainable support structures and institutional policies aligned with national and international standards, positioning the university for continued advancement in research data stewardship.
Keywords: Research Data Management; Cultural Change; Research Support Services